2000
DOI: 10.1039/a906180k
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic compounds as coatings on polymer particles and magnetic properties of the composite particles

Abstract: Spherical micron-sized polymer particles coated with magnetite have been prepared by a new method consisting of a two step process, in which iron compounds are coated on a micron-sized polymer core by controlled hydrolysis of FeCl 3 in the presence of urea, poly(vinylpyrrolidone) and hydrochloric acid. The thickness of the coating layer could be altered by adjusting the amount of FeCl 3 added to the system. Magnetic particles were obtained by treating the coated powders with hydrogen at moderate temperatures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…[29] Although both methods guarantee a uniform size for the final product, the loading of magnetic nanoparticles is relatively low and further surface modification of the product is often necessary. Ugelstad et al improved the deposition approach by using highly porous polymer beads to increase the surface/volume ratio of the host material.…”
Section: Polymer-based Composite Particlesmentioning
confidence: 99%
“…[29] Although both methods guarantee a uniform size for the final product, the loading of magnetic nanoparticles is relatively low and further surface modification of the product is often necessary. Ugelstad et al improved the deposition approach by using highly porous polymer beads to increase the surface/volume ratio of the host material.…”
Section: Polymer-based Composite Particlesmentioning
confidence: 99%
“…They have found applications in the area of dope [14], wave-guide [15], photo electricity [16], and photochromophores. Other studies have also shown that these procedures can be used for the preparation of polymer particles covered with copper and copper compounds [17], zirconium [18], iron [19], and titanium compounds [20] by controlled surface precipitation processes, which makes it possible to extend the use of these colloids to different areas of high technology.…”
Section: Introductionmentioning
confidence: 97%
“…Due to the tremendous practical interest, the magnetic nanomaterials are commonly combined onto various colloidal spheres to form composite materials with other functional materials by employing a deposition approach, layer-by-layer technique or some surface reactions [18][19][20][21][22][23][24][25]. Subsequently, magnetic hollow spheres could be obtained by the removal of template core from the preformed composites [14,15], similar to the widely used template synthesis of other kinds of hollow spheres [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%